2016
DOI: 10.1039/c5nj01970b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of disordered carbon from rice husks for lithium-ion batteries

Abstract: RH-derived carbon exhibits stable electrochemical performance. Moreover, the preparation process is very simple and low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 27 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…In order to further improve the electrochemical performance under the premise of sustainable development, much effort has been diverted to the exploration of carbonaceous materials prepared by pyrolyzing natural biomass, such as rice straw . rice husks, coffee shells, crop stalks and sisal . Among them, the use of rice husks to extract carbon materials has made some progress.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further improve the electrochemical performance under the premise of sustainable development, much effort has been diverted to the exploration of carbonaceous materials prepared by pyrolyzing natural biomass, such as rice straw . rice husks, coffee shells, crop stalks and sisal . Among them, the use of rice husks to extract carbon materials has made some progress.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the figure that the surface functional groups varied to some extent at different carbonization temperatures. Li et al 18 reported that carbonized carbon obtained at low temperature as the electrode material exhibited low initial coulombic efficiency. Because a large number of oxygen-containing functional groups exist on the surface of carbonized carbon, they cause an irreversible reaction.…”
Section: Resultsmentioning
confidence: 99%
“…5 The stacking of carbon layers was found to enhance the cyclic stability of LIBs. According to Li et al, 18 when the carbonization temperature was 500°C, the basic carbonization of RHs was completed, and a further increase in temperature affected the formation of the layered structure of carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous carbon materials, biochar is of particular interest because of its low cost and material consistency, which can be realized from abundant and nontoxic biomass precursors . Various precursors, such as lignin, pomelo pericarp, rice husk, litchi shells, and peanut shells, have been used to prepare biochar, which was commonly carbonized at 500–900 °C under argon atmosphere and followed by acid or alkaline‐washing to remove the impurities, and then applied in LIBs as high‐capacity electrode materials . Thus, the fabrication of SiO 2 /carbon composite will be a highly attractive idea.…”
Section: Introductionmentioning
confidence: 99%